2016
DOI: 10.4067/s0034-98872016000700013
|View full text |Cite
|
Sign up to set email alerts
|

Rol de la microbiota gastrointestinal en la regulación de la respuesta inmune

Abstract: The role of gut microbiota in the regulation of the immune response (Rev Med Chile 2016; 144: 910-916)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
0
8
0
6
Order By: Relevance
“…As is well acknowledged, an inappropriate response of mucosal immune system to the resident microbiota and other noxious antigens results in IBD. In the intestinal tract, host immune system (Alarcón, González, & Castro, 2016) along with the indigenous commensal microorganisms, including fungi, viruses, and bacteria maintain intestinal homeostasis (Hooper, Littman, & Macpherson, 2012). Recently, it has been indicated that TLR4 serve as the hub of immune responses to microbes in the gut.…”
Section: The Role Of Tlr4 In Ibdmentioning
confidence: 99%
“…As is well acknowledged, an inappropriate response of mucosal immune system to the resident microbiota and other noxious antigens results in IBD. In the intestinal tract, host immune system (Alarcón, González, & Castro, 2016) along with the indigenous commensal microorganisms, including fungi, viruses, and bacteria maintain intestinal homeostasis (Hooper, Littman, & Macpherson, 2012). Recently, it has been indicated that TLR4 serve as the hub of immune responses to microbes in the gut.…”
Section: The Role Of Tlr4 In Ibdmentioning
confidence: 99%
“…As is well acknowledged, IBD results from an inappropriate response of a dysfunctional mucosal immune system to the resident microbiota and other noxious antigens. In intestinal ecology, trillions of indigenous commensal microorganisms, including bacteria, fungi, and viruses ( 8 ), maintain homeostasis along with the elements of the host immune system ( 9 ). However, the introduction of an innate immune defect, for example, epithelial barrier leak and/or mucosal destruction can harm the otherwise beneficial host–microbe balance.…”
Section: Introductionmentioning
confidence: 99%
“…Estos resultados sugieren que la presencia de bacteria en la mucosa intestinal estaría asociada a EII, probablemente por una alteración en la microbiota intestinal o en la integridad de la barrera epitelial de los pacientes con posibles consecuencias en la regulación de la respuesta inmune local 22 . No obstante, sería interesante proyectar el análisis de la variación del número de bacterias en un protocolo de seguimiento de los pacientes y de su enfermedad, en relación a los período de actividad/ remisión.…”
Section: Discussionunclassified